Teachers’ fidelity to curriculum: an insight from teachers’ implementation of the Indonesian EFL curriculum policy - Iskandar (Center for Humanities and Innovation Studies, 2020)
While the notion of partnership has become the new genre of curriculum implementation, Indonesian government has decided to shift back to centralized curriculum policy by issuing the 2013 curriculum (K-13). The reason is that teachers are incapable of shaping their own school curriculum based on the National Standards of Education. Centralized curriculum policy leaves the classroom as the end of the chain of decisions in which the position of teachers is merely as implementers, rather than involved decision-makers. This type of curriculum clearly demands high degree of teachers’ fidelity. The purpose of this study is to investigate the extent to which EFL teachers faithfully commit themselves to fidelity approach to curriculum implementation of the K-13 at Senior High Schools in Makassar, Indonesia. Four EFL teachers were interviewed using ethnographic interviewing technique. The findings showed that these EFL teachers implement the K-13 with high degree of fidelity. The findings, however, indicate that these teachers’ commitment to fidelity approach split into two distinctive reasons: interactive and coercive. The former means that teachers adhered to K-13 because they perceived it as being comprehensible through their interaction with the K-13 documents, while the latter seemed to be influenced by the K-13 curriculum policy that was typically coercive and top down practice.